PENDIDIKAN KARAKTER MELALUI KEGIATAN MENDONGENG DI TK ABA KARANGDUWUR DAN TK MASYITHOH PETANAHAN KABUPATEN KEBUMEN - diamah fitriyyah (Jurnal Pendidikan Agama Islam, 2014)
This study was aimed to describe (1) character values of fairy tales, (2) the presentation of tales by the teacher, and (3) character values that affect daily life of the students. This was a naturalistic qualitative study. Data collection was done through observation, interviews, and documents. The results of this study show the following. (1) Character education that appears in fairy tales is religious values, honesty, discipline, hard working, creative, independence, curiosity, taking pleasure in reading, responsibility, tolerance, democracy, love of peace, communicativeness, awareness of environment and society. (2) The presentation of the fairy tale is by reading the fairy tales from a book, directly telling stories without props, and telling stories with props. The style of telling story with the sounds of figures, inserting chant in fairy tale, and ending by Al Quran, Hadis, or Arab proverb. (3) Character values that affect in dialy life of student are religious values, honest, discipline, hard working, independence, curiosity, responsibility, love of peace, communicativeness, awareness of environment and society.